Evaluation of the antibacterial and anticancer activities of some South African medicinal plants - Kambizi Learnmore; Li Shenwei; Oshima Yoshiteru; Hattori Toshio; Obi Chikwelu L; Bisi-Johnson Mary A; Eloff Jacobus N; Vasaikar Sandeep D (BMC, 2011)
Abstract Background Several herbs are traditionally used in the treatment of a variety of ailments particularly in the rural areas of South Africa where herbal medicine is mainly the source of health care system. Many of these herbs have not been assessed for safety or toxicity to tissue or organs of the mammalian recipients. Methods This study evaluated the cytotoxicity of some medicinal plants used, inter alia, in the treatment of diarrhoea, and stomach disorders. Six selected medicinal plants were assessed for their antibacterial activities against ampicillin-resistant and kanamycin-resistant strains of Escherichia coli by the broth micro-dilution methods. The cytotoxicities of methanol extracts and fractions of the six selected plants were determined using a modified tetrazolium-based colorimetric assay (3-(4, 5-dimethylthiazol)-2, 5-diphenyl tetrazolium bromide (MTT) assay). Results The average minimum inhibitory concentration (MIC) values of the plants extracts ranged from 0.027 mg/mℓ to 2.5 mg/mℓ after 24 h of incubation. Eucomis autumnalis and Cyathula uncinulata had the most significant biological activity with the least MIC values. The in vitro cytotoxicity assay on human hepatocarcinoma cell line (Huh-7) revealed that the methanol extract of E. autumnalis had the strongest cytotoxicity with IC50 of 7.8 μg/mℓ. Ethyl acetate and butanol fractions of C. uncinulata, Hypoxis latifolia, E. autumnalis and Lantana camara had lower cytotoxic effects on the cancer cell lines tested with IC50 values ranging from 24.8 to 44.1 μg/mℓ; while all the fractions of Aloe arborescens and A. striatula had insignificant or no cytotoxic effects after 72 h of treatment. Conclusions Our results indicate that the methanol fraction of E. autumnalis had a profound cytotoxic effect even though it possessed very significant antibacterial activity. This puts a query on its safety and hence a call for caution in its usage, thus a product being natural is not tantamount to being entirely safe. However, the antibacterial activities and non-cytotoxic effects of A. arborescens and A. striatula validates their continuous usage in ethnomedicine.